2015
DOI: 10.1590/0100-2945-062/14
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield and Postharvest Quality of Wax Apple as Affected by Naphthalene Acetic Acid Application

Abstract: -Results of this study represent the first report of the effect of Naphthalene Acetic Acid (NAA) on the pre and post harvest quality of wax apple fruit. The wax apple trees were spray treated with 0, 5, 10 and 20 mg L -1 NAA under field conditions during 2008 to 2011. The experiments were carried out in Completely Randomized Design (CRD) with six replications. Leaf chlorophyll content, chlorophyll fluorescence, photosynthetic yield, net photosynthetic rate, drymatter content of leaves and total soluble solids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…It was observed on girdled vines 7 and 11 days earliness compare to the control vines in 2013 and 2014, respectively. Thus our results are similar with the findings of [20] who reported that sugar contents increased in phloem ringed plants compared to the control.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was observed on girdled vines 7 and 11 days earliness compare to the control vines in 2013 and 2014, respectively. Thus our results are similar with the findings of [20] who reported that sugar contents increased in phloem ringed plants compared to the control.…”
Section: Discussionsupporting
confidence: 92%
“…The best-known effect of girdling is to interrupt the movement through the phloem of photosynthates produced by leaves. This increases carbohydrates and plant hormones in above parts of the girdle [20,14]. Each of these effects may be obtained by complete girdling at the proper time.…”
Section: Discussionmentioning
confidence: 99%
“…According to the TSS values, it was observed that girdling treatments accelerates ripening. Our results are in agreement with the findings of [17,[24][25][26][27][28].…”
Section: Resultssupporting
confidence: 93%
“…Vines are girdled in an attempt to improve fruit setting, maturation, quality and yield parameters [7,[17][18][19]. Girdling practices cut the movement in the phloem and change the hormonal balance [12].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, auxins such as naphthalene acetic acid (NAA) and naphthalene acetamide (NAD) play vital role in the fruit, closely related to changing carbohydrate level in treated fruits. It can promote the sink potential of the fruits, which is in direct proportion to the rate of fruit growth Miller et al (1987), enhanced nutrient uptake and increased the fruit growth and quality such as fruit size and weight, length, diameter and flesh to seed ratio (Tavakoli and Rahemi, 2014).The increase in fruit firmness might be due to the effect of NAA on decreasing the polygalacturonase enzyme activity, which increase the strength of glycosidic bonds and pectin content in cell wall of fruitsKhandaker et al, (2015). Consequently, this protects the peel and pulp of mature fruits to soften and reduced the ethylene production as well as improved pre and post-harvest quality of fruits.…”
mentioning
confidence: 99%